On the Growth of Infinite-Order Subharmonic Functions in ℂ
For infinite-order functions u subharmonic in \(C\) with given restrictions on the Riesz masses of a disk of radius r ∈ (0, +∞), we find majorants for the functions \(B( r,u ) = { | u( z ) |:| z | r }\) and \(0.5em\(\) B ( r,u ) = { | 0.5em\(\) u ( z ) |:| z | r }\) , where \(0.5em\(\) u\) is a function conjugate to u., number=9, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Kondratyuk, Ya. V., year=2002, month=Sep., pages=1276–1281